BCPT: Participant Update - K. Smigel (JNCI Journal of the National Cancer Institute, 1994)
Background Acute kidney injury (AKI) during vancomycin treatment remains a rare occurrence in adult patients with haematological malignancies (HMs). The objective of this multicentre study was to investigate the incidence and risk factors for AKI during vancomycin treatment in patients with HM. Methods The present study examined patients who were admitted to hospital and receiving vancomycin therapy between 2009 and 2024 at three tertiary hospitals. The primary outcome was the incidence of AKI during vancomycin treatment. Results The study comprised a total of 610 out of 982 patients. The incidence of AKI during vancomycin treatment among patients with HM was 13.0% (79/610). Multiple logistic regression analysis revealed that cardiac insufficiency (OR 3.305, 95% CI = 1.498-7.290, p = 0.003), chronic kidney disease (OR 5.074, 95% CI = 1.636-15.735, p = 0.005), hypoalbuminaemia (OR 2.930, 95% CI = 1.515-5.664, p = 0.001), concomitant spironolactone (OR 3.362, 95% CI = 1.586-7.290, p = 0.002) and chemotherapeutic drugs (OR 6.683, 95% CI = 2.025-22.051, p = 0.002) were independent risk factors for AKI during vancomycin treatment. Conclusion The occurrence of AKI in adult patients with HM during vancomycin treatment is a prevalent issue and is associated with a number of clinical and treatment-related factors. HM patients with cardiac dysfunction, chronic kidney disease, hypoalbuminaemia or concomitant spironolactone, chemotherapeutic agents may have a higher risk of AKI during vancomycin treatment.